Old Books and Digital Publishing: Eighteenth-Century Collections Online - Gregg, Stephen H. (Humanities, 2020)
This is a history of Eighteenth-Century Collections Online, a database of over 180,000 titles. Published by Gale in 2003 it has had an enormous impact of the study of the eighteenth century. An essential aspect of this Element is how it explores the socio-cultural and technological debates around the access to old books.